The Effectiveness Of Collaborative Product Advertising Between Erigo And Jkt48 Through Instagram Social Media Using The Aida Approach (Case Study On Instagram @Erigostore) - Agna Pahlevi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to measure the effectiveness of Erigo and JKT48 collaboration product advertisements through Instagram social media. Using purposive sampling method, data was collected from 120 respondents, who are Erigo's Instagram followers, through an online questionnaire distributed via Whatsapp and Instagram. Data were analyzed using SPSS version 29 with descriptive techniques, simple tabulation, and average user satisfaction scores using an interval scale. Validity and reliability tests of the questionnaire were carried out to ensure the accuracy of the instrument. The results showed that based on descriptive analysis, the advertisement fell into the “Very Good” and “Effective” categories on all four dimensions measured by the AIDA model. This research is expected to contribute to the knowledge and analysis of online media and corporate strategies to maintain profitability in a competitive market